New Approaches to Organization Design Theory and Practice of Adaptive Enterprises - Håkonsson, Dorthe Døjbak; Nielsen, Jørn Flohr; Snow, Charles C.; Ulhøi, John (Information and Organization Design Series, 2009)
Organization design (OD) is a key feature of management theory and practice. It addresses the challenges of constructing and maintaining effective organizations. Essential to its application is the assumption that it can improve organizations and their performance. Faced with the ever-accelerating pace of technological change and the restructuring of markets, many firms have questioned their own organizational structures and processes. Consequently, we have witnessed much organizational experimentation and the development of new forms of organizing over the last decade. How does organization design inform such experimentation? And how can organization design help managers gain insights and advance the current understanding of how organizations can meet environmental challenges and constraints in the future? This book is the third volume to emerge from a series of workshops on organization design, featuring new empirical research and theoretical insights. The chapters are organized around three central themes: (1) Towards New Organizational Forms; (2) Dynamics of Adaption and Change; and (3) Fit and Performance. The chapters cover such timely issues as organizational networks, virtuality, learning, dynamic capabilities, and adaptation. Common to all contributions is a focus on the core theories of OD and emerging perspectives. Collectively, the chapters reflect the state of the art of OD and provide a further step toward the evolution of this important field of research.